The long walk [videorecording (Blu-Ray)] - Mollner, JT; Hoffman, Cooper, 2003-; Jonsson, David, 1993-; Wareing, Garrett; Nyuot, Tut; Plummer, Charlie, 1999-; Wang, Ben, 1997-; Griffin Davis, Roman, 2007-; Gonzalez, Jordan; Odjick, Joshua; Hamilton, Josh; Greer, Judy, 1975-; et al. (Lionsgate, 2025)
"How far could you go? Fifty teenage boys are about to find out in the grueling competition called The Long Walk. Overseen by the merciless Major, the contest is the ultimate expression of every man for himself. To the walk's winner will go the ultimate prize: riches beyond belief... and any wish he desires. When local kid Garraty arrives at the starting line and meets McVries, they find a moving camaraderie amidst the peril of the walk. But the soul-crushing truth remains: Only one will survive. Walk or die."--